MULTILABEL MOOD CLASSIFICATION BASED ON INDONESIAN SONG LYRICS FEATURES - Ariyanto, Irvan
Research related to the classification of the mood of Indonesian songs has been carried out by previous researchers. However, this study only carried out single label classification, where in fact music can consist of more than one mood label. The multilabel classification of musical moods has also been carried out by previous researchers, but this study only used audio features. This study will perform a multi-label classification of Indonesian songs with lyrics only. Research on single label mood classification shows that the best results are only with the lyrics feature, which is superior to the audio feature and the combination of audio and lyrics. Song lyrics have a variety of language styles. The song that is inserted in the style of sarcasm changes the meaning and impression of the song. These problems can be handled with the detection of sarcasm.